Theoretical studies on anisotropic charge mobility, band structure, and non-linear optical calculations of ambipolar type organic semiconductors - Sahoo, Smruti R; Khatua, Rudranarayan; Debata, Suryakanti; Sharma, Sagar; Sahu, Sridha (2019)
The anisotropic charge carrier mobilities of two phenancene series compounds such as dibenzo[a,c]picene (DBP) and tribenzo[a,c,k]tetraphene (TBT) is investigated based on the first-principle calculations and Marcus-Hush theory. The molecular packing patterns in organic crystal play an important role for determing the charge carrier mobility and hence the device efficiencies designed from the organic materials. Among the studied molecules, TBT shows a maximum anisotropic hole ($μ_h=0.129\ cm^2V^{-1}s^{-1}$) and electron ($μ_h=1.834\ cm^2V^{-1}s^{-1}$) mobility, hence possesses an ambipolar semiconducting character. The frontier molecular orbital analyses proved the better air-stability of the studied compounds than the conventional pentacene, because of their higher HOMO energy levels. Band structure calculations of the studied compounds have also been investigated. From non-linear optical (NLO) properties anysis, we found the TBT compound shows more NLO response than DBP.